2005
DOI: 10.1002/qua.20447
|View full text |Cite
|
Sign up to set email alerts
|

Model density approach to the Kohn–Sham problem: Efficient extension of the density fitting technique

Abstract: ABSTRACT:We present a novel procedure for treating the exchange-correlation contributions in the Kohn-Sham procedure. The approach proposed is fully variational and closely related to the so-called "fitting functions" method for the Coulomb Hartree problem; in fact, the method consistently uses this auxiliary representation of the electron density to determine the exchange-correlation contributions. The exchange-correlation potential and its matrix elements in a basis set of localized (atomic) orbitals can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…Richer fitting basis sets gave further reductions in these errors for various observables, reaching essentially the results of the numerical procedure employing the exact density [81]. Atomisation energies have been reproduced up to about 1 kcal/mol for optimised molecular structures for standard auxiliary basis sets [81].…”
Section: Using the Fitted Density And Charge Distributionsmentioning
confidence: 97%
See 4 more Smart Citations
“…Richer fitting basis sets gave further reductions in these errors for various observables, reaching essentially the results of the numerical procedure employing the exact density [81]. Atomisation energies have been reproduced up to about 1 kcal/mol for optimised molecular structures for standard auxiliary basis sets [81].…”
Section: Using the Fitted Density And Charge Distributionsmentioning
confidence: 97%
“…For a moderate-sized fitting basis, it has been shown that the mean absolute errors of the model density approach, compared to using the KS density, were less than 0.5 pm for bond lengths and 0.3 for angles on a large set of molecules for both the local density and gradient corrected XC approximations [81,82]. Richer fitting basis sets gave further reductions in these errors for various observables, reaching essentially the results of the numerical procedure employing the exact density [81].…”
Section: Using the Fitted Density And Charge Distributionsmentioning
confidence: 98%
See 3 more Smart Citations